Structural and functional aspects of phytochemistry - Runeckles, V. C. (Victor C.); Tso, T. C. (Tien-Chioh) (Recent advances in phytochemistry, 1972)
Recent Advances in Phytochemistry, Volume 5: Structural and Functional Aspects of Phytochemistry covers the proceedings of the 10th Symposium of the Phytochemical Society of North America held in Beltsville College Park, Maryland on October 6-9, 1970. The book discusses the energy conversion in both photooxidation and photophosphorylation reactions of photosynthesis; and advances in phytochrome studies, including the physiological and biochemical characterization of the pigment, the mechanism of action, and the regulation of phytochrome-mediated processes. The text also describes the structure.